Novel CSF biomarkers in genetic frontotemporal dementia identified by proteomics. Issue 4 (7th March 2019) - van der Ende, Emma L.; Meeter, Lieke H.; Stingl, Christoph; van Rooij, Jeroen G. J.; Stoop, Marcel P.; Nijholt, Diana A. T.; Sanchez‐Valle, Raquel; Graff, Caroline; Öijerstedt, Linn; Grossman, Murray; McMillan, Corey; Pijnenburg, Yolande A. L.; et al.
Abstract: Objective: To identify novel CSF biomarkers in GRN ‐associated frontotemporal dementia (FTD) by proteomics using mass spectrometry (MS). Methods: Unbiased MS was applied to CSF samples from 19 presymptomatic and 9 symptomatic GRN mutation carriers and 24 noncarriers. Protein abundances were compared between these groups. Proteins were then selected for validation if identified by ≥4 peptides and if fold change was ≤0.5 or ≥2.0. Validation and absolute quantification by parallel reaction monitoring (PRM), a high‐resolution targeted MS method, was performed on an international cohort ( n = 210) of presymptomatic and symptomatic GRN, C9orf72 and MAPT mutation carriers. Results: Unbiased MS revealed 20 differentially abundant proteins between symptomatic mutation carriers and noncarriers and nine between symptomatic and presymptomatic carriers. Seven of these proteins fulfilled our criteria for validation. PRM analyses revealed that symptomatic GRN mutation carriers had significantly lower levels of neuronal pentraxin receptor (NPTXR), receptor‐type tyrosine‐protein phosphatase N2 (PTPRN2), neurosecretory protein VGF, chromogranin‐A (CHGA), and V‐set and transmembrane domain‐containing protein 2B (VSTM2B) than presymptomatic carriers and noncarriers. Symptomatic C9orf72 mutation carriers had lower levels of NPTXR, PTPRN2, CHGA, and VSTM2B than noncarriers, while symptomatic MAPT mutation carriers had lower levels of NPTXR and CHGA than noncarriers. Interpretation: We identified and validated five novel CSF biomarkers in GRN‐ associated FTD. Our results show that synaptic, secretory vesicle, and inflammatory proteins are dysregulated in the symptomatic stage and may provide new insights into the pathophysiology of genetic FTD. Further validation is needed to investigate their clinical applicability as diagnostic or monitoring biomarkers.